Quasi-particle–vibration coupling approach for nuclear β-decay - Colò, Gianluca; Niu, Yifei (Frontiers in Astronomy and Space Sciences, 2024)
The study of β-decay is important to answer open questions in physics and astrophysics; however, theoretical predictions of the associated half-lives are still plagued by uncertainties. In this short review, we argue that a reliable model for this study is nuclear density functional theory (DFT), complemented by further specific correlations; the quasi-particle–vibration coupling (QPVC) model has been successful in predicting half-lives in a number of spherical nuclei, and its extension to deformed systems should be envisioned. Some remaining open questions are addressed.